Gelatin- and starch-based hydrogels. Part A: Hydrogel development, characterization and coating. (5th November 2016) - Van Nieuwenhove, Ine; Salamon, Achim; Peters, Kirsten; Graulus, Geert-Jan; Martins, José C.; Frankel, Daniel; Kersemans, Ken; De Vos, Filip; Van Vlierberghe, Sandra; Dubruel, Peter
Highlights: Hydrogel films were developed consisting of methacrylamide-modified gelatin and starch-pentenoate building blocks. The mechanical properties of the hydrogels were determined by the DS of the gel-MA applied and the chemical composition (ratio gelatin/starch). The affinity of a bioactive aggrecan-coating for gelatin was successfully demonstrated. Abstract: The present work aims at constructing the ideal scaffold matrix of which the physico-chemical properties can be altered according to the targeted tissue regeneration application. Ideally, this scaffold should resemble the natural extracellular matrix (ECM) as close as possible both in terms of chemical composition and mechanical properties. Therefore, hydrogel films were developed consisting of methacrylamide-modified gelatin and starch-pentenoate building blocks because the ECM can be considered as a crosslinked hydrogel network consisting of both polysaccharides and structural, signaling and cell-adhesive proteins. For the gelatin hydrogels, three different substitution degrees were evaluated including 31%, 72% and 95%. A substitution degree of 32% was applied for the starch-pentenoate building block. Pure gelatin hydrogels films as well as interpenetrating networks with gelatin and starch were developed. Subsequently, these films were characterized using gel fraction and swelling experiments, high resolution-magic angle spinning 1 H NMR spectroscopy, rheology, infrared mapping and atomic force microscopy. The results indicate that both the mechanical properties and the swelling extent of the developed hydrogel films can be controlled by varying the chemical composition and the degree of substitution of the methacrylamide-modified gelatin applied. The storage moduli of the developed materials ranged between 14 and 63 kPa. Phase separation was observed for the IPNs for which separated starch domains could be distinguished located in the surrounding gelatin matrix. Furthermore, we evaluated the affinity of aggrecan for gelatin by atomic force microscopy and radiolabeling experiments. We found that aggrecan can be applied as a bioactive coating for gelatin hydrogels by a straightforward physisorption procedure. Thus, we achieved distinct fine-tuning of the physico-chemical properties of these hydrogels which render them promising candidates for tissue engineering approaches.